Comparative efficacy of different traditional mind-body exercises in patients with stable chronic obstructive pulmonary disease: a systematic review and network meta-analysis - Lin, Xiang; Xu, Qianqian; Xu, Wenshan; Sun, Wen; Sun, Hui; Xu, Shungui (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to systematically compare the differential therapeutic effects of various traditional mind–body exercises (TaiChi, Liuzijue, Wuqinxi, Baduanjin, Yijinjing, and Yoga) in patients with chronic obstructive pulmonary disease (COPD) through a network meta-analysis, providing evidence-based support and a scientific rationale for developing individualized rehabilitation strategies.MethodsA comprehensive search was performed to identify randomized controlled trials (RCTs) investigating traditional mind–body exercise interventions in COPD patients. Databases including PubMed, Embase, Web of Science, Cochrane Library, CNKI, WanFang, and the VIP Database were searched from their inception to June 2025. The methodological quality of included studies was assessed using Cochrane Risk of Bias tool, while the network meta-analysis was conducted in Stata 14.0 using the frequentist model. Publication bias was assessed using funnel plots.ResultsA total of 83 RCTs comprising 6,707 COPD patients were included. For improving the percentage of predicted forced expiratory volume in 1 s (FEV1%), the interventions ranked as follows: Wuqinxi (SUCRA = 82.9%) > Yijinjing (SUCRA = 65.9%) > Liuzijue (SUCRA = 63.5%) > Baduanjin (SUCRA = 63.1%) > Yoga (SUCRA = 47.8%) > TaiChi (SUCRA = 25.3%) > Conventional treatment (SUCRA = 1.5%). For enhancing the 6-min walk test (6MWT), the ranking was: Wuqinxi (SUCRA = 96.7%) > Baduanjin (SUCRA = 80.6%) > TaiChi (SUCRA = 53.1%) > Liuzijue (SUCRA = 49.1%) > Yoga (SUCRA = 42.9%) > Yijinjing (SUCRA = 26.8%) > Conventional treatment (SUCRA = 0.9%). For reducing the COPD Assessment Test (CAT) score, the ranking was: Yijinjing (SUCRA = 96.7%) > TaiChi (SUCRA = 75.9%) > Wuqinxi (SUCRA = 63.2%) > Baduanjin (SUCRA = 42.4%) > Yoga (SUCRA = 37.7%) > Liuzijue (SUCRA = 33.0%) > Conventional treatment (SUCRA = 1.2%).ConclusionWuqinxi demonstrated the greatest benefits in improving pulmonary function and exercise capacity, whereas Yijinjing showed the most significant effects in enhancing quality of life. Different mind–body exercise interventions may promote rehabilitation through distinct physiological and psychological mechanisms. Individualized selection of interventions can be tailored based on patients’ functional status and rehabilitation needs.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251051806, identifier CRD420251051806.